(untitled) (Práxis Educativa, 2025)
This article aims to present possible thematizations based on the theoretical framework of the social philosopher Zygmunt Bauman, considering the wide range of analyses, thoughts, and understandings that emerge from it. Bauman’s theoretical construction seems to indicate diversity and plurality as inherent features of the human condition and to point to a dialogical attitude as a constitutive possibility of the shared world. The awareness of an ambivalent paradigm guides and shapes the methodology of this text, since meanings and language, in their contingencies, place dialogue among different others at the center of democratic and republican consensuses, in addition to illuminating Bauman’s broad theoretical horizon through the path of pluralizing or sociological hermeneutics, forged in the dialogue between hermeneutic and dialectical conceptions. Ambivalence/plurivalence may enable a shared world, even if centered on the individual, open to an education for dialogue and solidarity. Keywords: Ambivalence. Dialogue. Solidarity.